When Adam Delved and Eve Span who was then the Gentleman by Natee Utarit - Ariyasaj, Rungroj (Silpa Bhirasri (Journal of fine arts), 2021)
This article aims to present the content and meaning in the work of art When Adam Delved and Eve Span who was then the Gentleman? by Natee Utarit. As this set of painting is dissimilar from any other altarpieces in many respects, for example the context of creation, the non-Christianity stories and the use of Christianity symbols to convey meaning in conjunction with Appropriation art, these various symbols require a coherent interpretation, study of the symbols that appear in this art work is interesting in terms of its connection with historical events. For the benefit of viewers’ rendition who have different beliefs and cultures. The result of the study in field of historical sources, for instance, social, political and art history including with the Bible showed that there are two events presented the references of social inequality such as the British Agricultural Revolution in the 14th century and the Western European colonization during the 16th-18th century.